2021
DOI: 10.1038/s41577-021-00583-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mucosal vaccines — fortifying the frontiers

Abstract: The global burden of mortality and morbidity associated with infectious diseases caused by mucosal pathogens remains unacceptably high. Indeed, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic provides a brutal reminder of the continual threat of novel mucosal infectious challenges, in addition to the threat posed by many widespread mucosal infections for which no or only suboptimal vaccines exist. Now more than ever, there is a clear focus on vaccine requirements for respiratory patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
448
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(455 citation statements)
references
References 189 publications
(220 reference statements)
3
448
0
4
Order By: Relevance
“…VE was also higher in individuals aged 18-34 years than in individuals aged 35-64 years for both ChAdOx1 and BNT162b2 (heterogeneity P = 0.002 and P = 0.001, respectively). However, there was no evidence of differences between individuals reporting versus not reporting long-term health conditions or between <6 versus ≥6 weeks (median (IQR) 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) versus 72 (63-77) d) between the first and second BNT162b2 vaccination (heterogeneity P = 0.18; Supplementary Table 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VE was also higher in individuals aged 18-34 years than in individuals aged 35-64 years for both ChAdOx1 and BNT162b2 (heterogeneity P = 0.002 and P = 0.001, respectively). However, there was no evidence of differences between individuals reporting versus not reporting long-term health conditions or between <6 versus ≥6 weeks (median (IQR) 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) versus 72 (63-77) d) between the first and second BNT162b2 vaccination (heterogeneity P = 0.18; Supplementary Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…One explanation could be differential effects of vaccination on mucosal and systemic immunity 20 . In theory, the former is more important for preventing carriage, transmission and infection becoming established, whereas the latter is more important for preventing severe disease once infected 21 . Studies in rhesus macaques showed greater reductions in SARS-CoV-2 viral load in the lungs and prevention of pneumonia, without reducing viral loads in the upper respiratory tract with intramuscular ChAdOx1 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be differential effects of vaccination on mucosal and systemic immunity 25 . In theory, the former is more important for preventing carriage, transmission, and infection becoming established, while the latter is more important for preventing severe disease once infected 26 . Studies in rhesus macaques showed greater reductions in SARS-CoV-2 viral load in the lungs and prevention of pneumonia, without reducing viral loads in the upper respiratory tract with intramuscular ChAdOx1 27 , and protection against viral replication at much lower concentrations in the lower than the upper respiratory tract with intramuscular mRNA-1273 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aberrations in cellular density have been associated with disease states such as inflammatory bowel disease (IBD). As the intestine is the largest immune organ in the body 14 , evaluating immune cell localization and cellular interactions in the gut is critical for understanding oral vaccine design 15 , interactions regulating the gut microbiota 16 , regulation of allergic food responses 17 , axes critical for wound repair 18 , and immune system responses and immunotherapies for cancer [19][20][21][22] .…”
Section: Codex Multiplexed Imaging Of the Small Intestine And Colonmentioning
confidence: 99%